Jane Austen and masculinity - Kramp, Michael (Transits (Bucknell University), 2018)
Jane Austen and Masculinity is an eclectic collection of contemporary scholarship addressing the representation of men and masculinity in the fiction and popular adaptations of Austen. This anthology includes work by a variety of esteemed and emergent Austen scholars from around the world who engage in a dialogue on critical questions surrounding her fictional treatment of men and masculinity, such as historical (post-French Revolutionary) changes in social expectations for men and women, brothers and fathers, male lovers, soldiers and the military, queer and alternative sexualities, violence, and male devotees of Austen. The collection addresses Austen's fiction, including her juvenilia, as well as the ongoing popular appeal of her work and the enduring Austen vogue. The work in this anthology builds on established critical discourses in Austen scholarship as well as important conversations in Masculinity Studies.